PENGARUH SELF-EFFICACY, MOTIVASI BELAJAR, DAN KETERAMPILAN DIGITAL TERHADAP KESIAPAN KERJA LULUSAN FEBM UNIVERSITAS MARITIM RAJA ALI HAJI TAHUN 2025 - Laila Desmita Angrainny; Bunga Paramita; Firmansyah Kusasi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of self-efficacy, learning motivation, and digital skills on the work readiness of graduates from the Faculty of Maritime Economics and Business, Raja Ali Haji Maritime University in 2025. This research was motivated by the increasing demands of the digital workforce, requiring graduates to possess mental readiness, adaptability, learning motivation, and adequate digital skills. This study employed a quantitative approach with an associative research design. The population consisted of 194 FEBM UMRAH graduates in 2025, with a sample of 130 respondents determined using the Isaac and Michael formula at a 5% error rate. The sampling technique used was purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS software. The results showed that self-efficacy, learning motivation, and digital skills had a positive and significant effect on work readiness both partially and simultaneously. This indicates that the higher the self-efficacy, learning motivation, and digital skills possessed by graduates, the higher their work readiness in facing competition in the digital era workforce.